Effect of short-term ageing temperature on bitumen properties. (8th May 2017) - Hofko, B.; Cannone Falchetto, A.; Grenfell, J.; Huber, L.; Lu, X.; Porot, L.; Poulikakos, L. D.; You, Z.
Abstract : Properties of asphalt mixtures after ageing are fundamental parameters in determining long-term performance (e.g. durability) of these materials. With increasing popularity of reduced temperature mixtures, such as warm-mix asphalt, WMA, the question remains how a reduction in short-term ageing affects the properties after long-term ageing of bituminous materials. This paper aims to improve our understanding of the effect of asphalt manufacturing temperature on ageing and the resulting mechanical properties of bituminous binder by studying the effect of short- and long-term ageing of different bitumen samples as a function of short-term ageing temperatures. For this purpose, round robin experiments were conducted within the RILEM technical committee (TC) 252 chemo-mechanical characterisation of bituminous materials by 10 laboratories from 5 countries using four binders of the same grade (70/100 pen) from different crude sources. The short-term ageing was carried out using the standard procedure for rolling thin film oven test (RTFOT), but varying the temperatures. Long-term ageing was carried out using the standard procedure for pressure aging vessel (PAV) in addition to RTFOT. For the mechanical characterisation, rheological data were determined by using the dynamic shear rheometer (DSR) and conventional tests, with needle penetration and softening point using the ring and ball method. The results show that although different short-term ageing temperatures showed a significant difference in the mechanical properties of the binders, these differences vanished after long-term ageing with PAV.